Visual characterization of heated water spray jet breakup induced by full cone spray nozzles - Naz, M.Y. (Maik Nauka-Interperiodica Publishing, 2015)
The present work with specific objectives places a greater emphasis on measurements of the breakup lengths and phenomenological analysis of a hot water jet under reduced pumping pressures in still environment. Therefore, visual and comparative studies are conducted on full cone jet disintegration of heated water for low pumping pressures. A further analysis of the grabbed images confirms the strong influence of the input processing parameters on full cone spray patternation. It is also predicted that the heated liquids generate a dispersed spray pattern by utilizing partial evaporation of the spraying medium. The radial spray cone width and angle do not vary significantly with increasing Reynolds and Weber numbers at early injection phases, leading to enhanced macroscopic spray propagation. The discharge coefficient, mean flow rate, and mean flow velocity are significantly influenced by the load pressure, but less affected by the temperature. The fine scale image analysis also predicts toroidal-shaped vortex formation in the spray structure near the water boiling point. Â© 2015, Pleiades Publishing, Ltd.